EKSISTENSI DAN MAKNA SIMBOLIK TRADISI LABUH PADA MASYARAKAT DUSUN KUMBO DESA GUMIRIH KECAMATAN SINGOJURUH KABUPATEN BANYUWANGI TAHUN 1988 – 2023 - Hairul Agustian; Mahfud; Sahru Romadloni; I Kadek Yudiana (Yayasan Nusantara Hasana Berdikari, 2023)
The Labuh tradition is one of the traditions that grows and develops in Banyuwangi Regency, precisely in Kumbo Hamlet, Singojuruh District. This study aims to examine the historical and symbolic meaning of the Labuh tradition, which includes: 1) What is the history of the Labuh tradition, 2) What is the symbolic meaning and procession of the Labuh tradition, 3) What is the existence of the Labuh tradition from the role of the community, reasons for preservation, to the benefits of the Labuh tradition. This study used qualitative research methods. The results of this study can be summarized as follows: 1) The Labuh tradition began to emerge and develop in Dusun Kumbo which was initially introduced by Wono Rekso with the initial aim of being a means of salvation after carrying out tripe on the base and then experiencing a shift in function to become salvation before harvest, 2) The symbolic meaning of the Labuh tradition can be seen from the form of objects, prayers, and processions which illustrate that achieving something must be accompanied by sincere intentions and a clean heart, 3) The Dusun Kumbo community plays an important role in relation to the existence of the Labuh tradition until it still exists today